Gem-bearing granitic pegmatites in Malawi: their mineralogy, geochemistry, age, and fluid compositional variations - Kankuzi, Charles Frienderson (Rhodes University, Faculty of Science, Department of Geology, 2019)
The gem bearing granitic pegmatites from different pegmatite fields across Malawi intrude all important geological entities from the Palaeoproterozoic in the north, the Mesoproterozoic in central Malawi and the Pan-African basement in the south. U/Pb zircon and Rb/Sr mineral isochron ages indicate pegmatite emplacement from the Palaeoproterozoic to Pan-African and Mesozoic time. Most pegmatites are related to the Pan-African cycle; no Mesoproterozoic pegmatites were observed in this study. Within the Pan-African pegmatite groups there are two important subgroups. Some pegmatites show Sr isotopic compositions that indicate mantle components contributing to the parental granites from which the pegmatites evolved. Others show higher Sr initials, indicating crustal granites as primary pegmatite sources or significant crustal contamination. Only for few pegmatites, such as the Palaeoproterozoic and Ordovician gem tourmaline pegmatites in the Chitipa and Dowa Districts, the granitic source is evident from their field context. For all others the granitic origin is interpreted by mineralogical and geochemical evidence. All analysed pegmatites belong to either the Rare Element Class or the Miarolitic Class, but they vary in their degree of fractionation. The more evolved pegmatites are more enriched in incompatible elements such as Be, Li, B, and Ta, which resulted in the formation of gem minerals such as beryl, aquamarine, tourmaline and topaz, which may or may not be associated with tantalite. The Rare Element pegmatites can be further subdivided into the REL-Li subclass, beryl type, beryl-columbite subtype, and in the complex type and elbaite subtype. The Miarolitic pegmatites include Mi-Li subclass and beryl-topaz type. Fluid inclusion studies (heating-cooling stage, Raman spectroscopy) identified a variety of fluid compositions that were present at different times and different places, indicating a variety of fluid sources. They range from aqueous-saline to CO2"“rich carbonic fluids (CO2 +C3H8+ N2), or aqueous-carbonic fluids (H2O-CO2-CH4 and H2O-CO2-H2-H2S-CH4). The dominant solutes and species for the pegmatites show genetic variations over time and orogen (Paleo-/Meso-/Neoproterozoic). Uniform homogenisation temperatures and salinities in individual samples indicate that the gem-bearing pegmatites contained homogeneous fluids at the time of their capturing in quartz. Based on fluid inclusion data, the estimated trapping conditions of inclusions in quartz for all studied pegmatites except for one pegmatite suggest low pressures between 0.9 to 2.6 kb at temperatures of 400-600 ï‚°C. The other pegmatite formed at slightly higher pressures of 2.2 to 3.6 kb. However, the pressure range for all the pegmatites is in agreement with the known liquidus conditions of Rare-Element pegmatite crystallisation. The shallow crustal emplacement level (3.4-9.8 km) and the greater depth (8.3 to 13.6 km) favoured the formation of gemstones.
Keywords: Granite; Pegmatites; Geochemistry; Fluid inclusions; Nonferrous metals